1990
DOI: 10.1177/003368829002100201
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Rhetorical Organization in Expository Prose on ESL Readers in Singapore

Abstract: This paper reports an experimental study carried out at the In stitute of Education in 1987 to find out the effects of rhetorical organization in expository prose on ESL readers in Singapore. The study was undertaken mainly to test the findings of a study by Carrell (1984) on ESL readers in USA. As an extension of the earlier study, which used foreign students at an American university as subjects, the present study incorporated three levels of language proficiency: school, college* and university graduates. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…According to the results of the cline procedure, the process essay was reported to be the easiest, followed by argumentation, contrast, narrative, and description. Although the purpose of this study was not to provide a taxonomy, these results offer an important contribution to rhetorical organization taxonomy literature (Carrell, 1984b;Fooh, 1989;Freedle & Kostin, 1991Goh, 1990;Lei, 2010;Meyer & Freedle, 1984;Sharp, 2002;Talbot et al, 1991;Yali & Jiliang, 2007;Zhang, 2008), as previous studies have not sufficiently reported the reading levels of texts and participants. This study also furthers the discussion as the essays (and accompanying analysis) are identified with terms commonly used in modern composition texts (i.e., process, description, narrative, cause/effect, comparison/contrast, and argumentation/persuasion), thus facilitating interpretation and replication.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…According to the results of the cline procedure, the process essay was reported to be the easiest, followed by argumentation, contrast, narrative, and description. Although the purpose of this study was not to provide a taxonomy, these results offer an important contribution to rhetorical organization taxonomy literature (Carrell, 1984b;Fooh, 1989;Freedle & Kostin, 1991Goh, 1990;Lei, 2010;Meyer & Freedle, 1984;Sharp, 2002;Talbot et al, 1991;Yali & Jiliang, 2007;Zhang, 2008), as previous studies have not sufficiently reported the reading levels of texts and participants. This study also furthers the discussion as the essays (and accompanying analysis) are identified with terms commonly used in modern composition texts (i.e., process, description, narrative, cause/effect, comparison/contrast, and argumentation/persuasion), thus facilitating interpretation and replication.…”
Section: Discussionmentioning
confidence: 77%
“…Logical organizationwas again, as was done in the questionnaire, cited as a primary feature by eight (80%) of the informants (Annie, Ben, Eve, Harold, Jacob, Linda, Marsha, Nelson).Examining the informants' responses, their perceptions appeared to stem from an entangled mix of two causes: (a) the informants' awareness of (or lack of awareness of) the type of rhetorical organization exemplified in the essays and therhetorical organization of the essays themselves. Eve illustrated an example of both by demonstrating a strong awareness of rhetorical structure by naming the rhetorical organization of each essay, explaining that she felt each organization style was easier than the last.Eve's comments are related to previous taxonomy literature which reported that the logical organization of a text can impact readers' perceptions of difficulty (Bereiter, 1978 as cited in Calfee & Curley, 1984;Carrell, 1984a;Fooh, 1989;Freedle & Kostin 1991Goh, 1990;Lei, 2010;Meyer & Freedle, 1984;Lei, 2010;Sharp, 2002;Talbot, Ng, & Allan, 1991;Yali & Jiliang, 2007;Zhang, 2008).A second informant, Ben, further demonstrated how a lack of awareness can play a part.Discussing the contrast organization of the "Grammy Rewards" essay and the essay's place in his cline, he pointed out that he felt that the essay's point-by-point structure was hard to understand because "the two grandmothers show up in the same paragraph. "Ben's report supports literature which explains that a readers' "knowledge relative to the formal, rhetorical organizational structures of different types of texts" (Carrell 1987, p. 481) contributes to perceptions of difficulty.…”
Section: Primary Featurementioning
confidence: 83%
“…That is, some text types are more complex than others, learners’ awareness can affect understanding (Flick & Anderson, 1980), and rhetorical structures are not constant across cultures (Kaplan, 1966, 2005). Nevertheless, taxonomy explorations have attempted to provide as distinctive a picture as possible (see Alkhaleefah, 2017; Amiri et al, 2012; Baker, 2021; Carrell, 1984a; Freedle & Kostin, 1991, 1993; Goh, 1990; Lei, 2010; Meyer & Freedle, 1984; Putra, 2012; Saadatnia et al, 2016; Salmani, 2010; Sharp, 2002; Talbot et al, 1991; Yali & Jiliang, 2007; Zhang, 2008). However, the results have generally been incongruent due mostly to varying text types under study, methodology, and participants’ reading levels (Baker, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%